Personal protective equipment in dental care during covid-19. A review. - Ruiz-Quilcat, Cristina (2022)
COVID-19 evidenced the need for preventive protocols to control its spread worldwide. Therefore, the purpose of this review was to compare the current indications and regulations for the use of personal protective equipment (PPE) in dental care. For the bibliographic search, keywords such as “Containment of Biohazards”, “Personal Protective Equipment”, “dental office”, “COVID-19” were used during the advanced search in Pubmed and academic Google. Forty regulations were obtained that met all the selection criteria for preventive measures through the use of PPE by the operator and the patient; being more detailed the Sanitary Directive 100-MINSA published in 2020 without evidence of updating in this year 2021. Likewise, in studies carried out on the reuse of masks, it was determined that the most effective method was decontamination with UV-C, which maintains their integrity and filtering capacity.